Synthesis and Characterization of Bipyridyl-(Imidazole)n Mn(II) Compounds and Their Evaluation as Potential Precatalysts for Water Oxidation - Ge Mu; Ryan B. Gaynor; Baylee N. McIntyre; Bruno Donnadieu; Sidney E. Creutz (Molecules, 2023)
Metalloenzymes make extensive use of manganese centers for oxidative catalysis, including water oxidation; the need to develop improved synthetic catalysts for these processes has long motivated the development of bioinspired manganese complexes. Herein, we report a series of bpy-(imidazole)n (n = 1 or 2) (bpy = 2,2′-bipyridyl) ligands and their Mn2+ complexes. Four Mn2+ complexes are structurally characterized using single-crystal X-ray diffraction, revealing different tridentate and tetradentate ligand coordination modes. Cyclic voltammetry of the complexes is consistent with ligand-centered reductions and metal-centered oxidations, and UV-vis spectroscopy complemented by TD-DFT calculations shows primarily ligand-centered transitions with minor contributions from charge-transfer type transitions at higher energies. In solution, ESI-MS studies provide evidence for ligand reorganization, suggesting complex speciation behavior. The oxidation of the complexes in the presence of water is probed using cyclic voltammetry, but the low stability of the complexes in aqueous solution leads to decomposition and precludes their ultimate application as aqueous electrocatalysts. Possible reasons for the low stability and suggestions for improvement are discussed.